Frequent falls and confusion: recurrent hypoglycaemia in a patient with tuberous sclerosis complex - Comninos,A; Yang,L; Abbara,A; Dhillo,W; Bassett,J; Todd,J (Clinical Case Reports, 2018)
Recurrent hypoglycaemia is common, but its presentation is often insidious resulting in delays in diagnosis and significant morbidity. We describe a case of an insulinoma presenting with falls and confusion in a patient with Tuberous Sclerosis, demonstrating the importance of early hypoglycaemia identification and a potential shared molecular pathogenesis.